POLITICAL CARICATURE AS AN ELEMENT OF RUSSIA’S HYBRID WAR AGAINST UKRAINE (2014-2022) - Gaiko, Oleg; Chaika, Oksana (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
The article deals with the political caricature of Russia in the Russian-Ukrainian war (2014-2022). It is shown that since 2014, Russia has systematically and consistently implemented a hybrid war against Ukraine, in which political actions were more important than military actions. The authors emphasize such an important element of the hybrid war against Ukraine as the implementation of the so-called "Gerasimov Doctrine" as evidence of the transformation of wars in 21st century. The main features and main objectives of Russian political caricature, as well as some approaches to hybrid warfare, are analyzed, and the main ideological narratives of Russian political caricature as an element of Russia’s hybrid war against Ukraine (2014-2022) are highlighted. The role of social networks as a convenient tool for the dissemination of Russian political caricature is revealed. It is shown that political caricature was one of the important elements of Russia’s political propaganda in the context of the Russian-Ukrainian war of 2014-2022. The basic features and main tasks of Russian political caricature in Russia’s hybrid war against Ukraine are considered, the main features and main tasks of Russian political caricature aimed at forming the desired emotional reaction are highlighted. The main ideological narratives of Russian political caricature during the Russian-Ukrainian war (2014-2022) are traced. The authors analyze the reaction of Russian political propaganda (on the example of political caricature) to the statements of the international community regarding Russia’s actions in the Russian-Ukrainian war. It is shown that the Russian political caricature was quite effective and promptly responded to political challenges (especially to the reactions of the international community to Russia’s actions in the Russian-Ukrainian war).